2017
DOI: 10.1139/cjfas-2016-0306
|View full text |Cite
|
Sign up to set email alerts
|

Fish community assessment with eDNA metabarcoding: effects of sampling design and bioinformatic filtering

Abstract: Species richness is a metric of biodiversity that represents the number of species present in a community. Traditional fisheries assessments that rely on capture of organisms often underestimate true species richness. Environmental DNA (eDNA) metabarcoding is an alternative tool that infers species richness by collecting and sequencing DNA present in the ecosystem. Our objective was to determine how spatial distribution of samples and "bioinformatic stringency" affected eDNA-metabarcoding estimates of species … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
169
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 174 publications
(181 citation statements)
references
References 39 publications
10
169
2
Order By: Relevance
“…This result would imply that the eDNA of stocked fish is well homogenized in the ponds, and the eDNA signal released by the introduced species is too low to influence the spatial distribution pattern of the entire fish community present in the ponds. This result is in agreement with Evans et al () who do not find a significant relationship between sample dissimilarity and geographic distance in a 22,000 m 2 surface area reservoir in which fish distribution is relatively homogeneous. By contrast, Sato, Sogo, Doi, and Yamanaka () indicated that geographic distances among sampling locations within lakes ranging in size from 84,000 to 2,219,000 m 2 have a significantly positive correlation with the abundance‐based community dissimilarity index resulting from spatial heterogeneity of eDNA distribution.…”
Section: Discussionsupporting
confidence: 93%
“…This result would imply that the eDNA of stocked fish is well homogenized in the ponds, and the eDNA signal released by the introduced species is too low to influence the spatial distribution pattern of the entire fish community present in the ponds. This result is in agreement with Evans et al () who do not find a significant relationship between sample dissimilarity and geographic distance in a 22,000 m 2 surface area reservoir in which fish distribution is relatively homogeneous. By contrast, Sato, Sogo, Doi, and Yamanaka () indicated that geographic distances among sampling locations within lakes ranging in size from 84,000 to 2,219,000 m 2 have a significantly positive correlation with the abundance‐based community dissimilarity index resulting from spatial heterogeneity of eDNA distribution.…”
Section: Discussionsupporting
confidence: 93%
“…As species detections via eDNA metabarcoding increase spatially or during repeated sampling, and as the relative species sequence abundance increases (e.g., one or few vs. thousands of AIS sequences), the likelihood of a spurious detection (i.e., a false-positive) in the site decreases (Evans et al, 2017;Jerde et al, 2011). As species detections via eDNA metabarcoding increase spatially or during repeated sampling, and as the relative species sequence abundance increases (e.g., one or few vs. thousands of AIS sequences), the likelihood of a spurious detection (i.e., a false-positive) in the site decreases (Evans et al, 2017;Jerde et al, 2011).…”
Section: Aquatic Invasive Species Detectionsmentioning
confidence: 99%
“…Most molecular methods used for these purposes can be categorized under the following two main approaches: (a) Targeted methods, which use species‐specific primers and techniques such as quantitative polymerase chain reaction (qPCR; e.g., Sigsgaard, Carl, Møller, & Thomsen, ; Smith, Wood, Mountfort, & Cary, ; Wood, Zaiko, Richter, Inglis, & Pochon, ); and (b) Community‐wide characterization methods, which use universal primers that enable entire communities or groups of organisms to be described, e.g., metabarcoding (Thomsen et al, ; Wood et al, ; Hänfling et al, ; Bista et al, ). While both targeted and community‐wide characterization methods have now been applied widely in a range of habitats (Dowle, Pochon, Banks, Shearer, & Wood, ; Evans et al, ; Laroche et al, ), few studies have directly compared the sensitivity of techniques (Pochon, Bott, Smith, & Wood, ). This is particularly important when these methods are applied with the aim of detecting rare or invasive species (Cristescu & Hebert, ; Goldberg et al, ).…”
Section: Introductionmentioning
confidence: 99%